Law Protection Mecanism of Wage Equality for Women Worker: Indonesian Law and Human Right Perspective - Sukarmi, Sukarmi; Ganindha, Ranitya; Umar, Azahlia (Brawijaya Law Journal, 2020)
Women labours in Indonesia still experiencing wage discrimination with male labours for works of equal value. Indonesia's efforts to provide protection against discrimination in wage for women labor is by ratifying ILO Convention No. 100 of 1951 and the CEDAW Convention 1979. This journal aims to find out the form of Protection of Wage Discrimination for women labours in Indonesia in accordance with the mandate of the ILO and CEDAW Conventions and the Protection Mechanism of wage discrimination given by Indonesia to women labours. This journal is a normative study, with a statute approach and a conceptual approach. This journal analyzes that the form of Protection of Wage discrimination Against women labours in Indonesia is through legislative action through ratification of ILO Convention No. 100 of 1951 with Law No. 80 of 1957 concerning the approval of ILO Conventions No. 100 Regarding Wages for Men and Women for Work of Equal Value, especially those contained in Article 1 letter (b) and Article 2, the ratification of CEDAW through Law No. 7 of 1984 concerning Ratification of the Convention Concerning the Elimination of All Forms of Discrimination Against Women especially those contained in Article 11 Letter (d), Law No. 13 of 2003 concerning Employment specifically regulated generally in Article 5, Article 6, and Article 88 Paragraph (3) Letter (i). This journal finds that Indonesia does not yet have regulations that contain special protection mechanisms for wage discrimination provided by Indonesia to women workers in the form of sanctions, reporting mechanisms or special supervision of discriminatory practices, which are not yet regulated either in the Employment Act or the Law ratified by the Convention ILO and CEDAW.